2013
DOI: 10.1016/j.jcol.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Transanal minimally-invasive surgery (TAMIS): Technique and results from an initial experience

Abstract: Transanal endoscopic microsurgery is a minimally-invasive approach for rectal lesions. Superior exposure and access to the entire rectum result in lesser risk of compromised margins and lower recurrence rates, when compared to conventional transanal excision. The aim of this study was to describe a single institution's initial experience with transanal minimally invasive surgery (TAMIS). This was a prospective review of our database. Eleven procedures from January 2012 to June 2013 were analyzed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Today, for this procedure there are several ways to a perineal approach with TEO and TAMIS. 23,24 In these studies, their authors proved that the use of the several tools equipment found in the market to carry out TAMIS is viable, and this is true also for the equipment for TEO.…”
Section: Discussionmentioning
confidence: 95%
“…Today, for this procedure there are several ways to a perineal approach with TEO and TAMIS. 23,24 In these studies, their authors proved that the use of the several tools equipment found in the market to carry out TAMIS is viable, and this is true also for the equipment for TEO.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, while comparing transanal resection, each has its advantages and considerations. Transanal resection, such as TEM or TAMIS (Transanal Minimally Invasive Surgery), offers the potential for organ preservation and shorter recovery time compared to more extensive surgical procedures [27]. Radiotherapy, particularly when combined with chemotherapy, is often employed in locally advanced cases to improve local control and increase the chances of successful surgical resection [28].…”
Section: Comparative Analysismentioning
confidence: 99%
“…Peritoneal entry represents a well-known complication of TAMIS and it is described more frequently when tumors are located anteriorly in the middle or upper rectum [12] . When it occurs (1% of cases [12] ), it is recommended to use a steep Trendelenburg position to facilitate wall repair and to convert to laparoscopy if it is impossible to maintain an adequate pneumorectum [22][23][24] . With this regard, some authors suggest placing the patients in a prone position to limit the amount of CO 2 passing into the peritoneal cavity [25] .…”
Section: Tamis: Technical Aspects and Indicationsmentioning
confidence: 99%